Hemolytic anemia as a presenting manifestation of Wilson's disease - Özsoylu, Şinasi; Koçak, Nurten; Yetgin, Sevgi (The Turkish Journal of Pediatrics, 1980)
An eighth year old girl with hepatosplenomegaly, spider nevi, hypoceruloplasminemia, hypercupriuria, portal hypertension due to post necrotic cirrhosis and decreased level of lipid soluble vitamins had marked hemolytic anemia. Hypoceruloplasminemia was also detected in both parents. The diagnosis of Wilson's disease was made with the above findings and her short durated hemolytic anemia was considered to be related to her disease. It was suggested that her hypercupremia was more destructive on her erythrocytes in the presence of vitamin E deficiency.